Characterizing OPRM1 DNA methylation in prescription opioid users with chronic musculoskeletal pain. (24th November 2022) - Sheikh, Sophia; Smotherman, Carmen; Patel, Monika; Langaee, Taimour; Wang, Danxin; Swaray, Edward; Velasquez, Esteban; Schmidt, Siegfried O.F.; Hendry, Phyllis; Cavallari, Larisa H.; Fillingim, Roger B.
Abstract : μ-opioid receptor 1 methylation varied by pain comorbidity, substance abuse history, reading level, and duration of prescription opioid use. Abstract: Introduction: Many patients with chronic pain use prescription opioids. Epigenetic modification of the μ-opioid receptor 1 ( OPRM1 ) gene, which codes for the target protein of opioids, may influence vulnerability to opioid abuse and response to opioid pharmacotherapy, potentially affecting pain outcomes. Objective: Our objective was to investigate associations of clinical and sociodemographic factors with OPRM1 DNA methylation in patients with chronic musculoskeletal pain on long-term prescription opioids. Methods: Sociodemographic variables, survey data (Rapid Estimate of Adult Health Literacy in Medicine-Short Form, Functional Comorbidity Index [FCI], PROMIS 43v2.1 Profile, Opioid Risk Tool, and PROMIS Prescription Pain Medication Misuse), and saliva samples were collected. The genomic DNA extracted from saliva samples were bisulfite converted, amplified by polymerase chain reaction, and processed for OPRM1 -targeted DNA methylation analysis on a Pyrosequencing instrument (Qiagen Inc, Valencia, CA). General linear models were used to examine the relationships between the predictors and OPRM1 DNA methylation. Results: Data from 112 patients were analyzed. The best-fitted multivariable model indicated, compared with their counterparts, patients with > eighth grade reading level, degenerative disk disease, substance abuse comorbidity, and opioid use < 1 year (compared with >5 years), had average methylation levels that were 7.7% (95% confidence interval [CI] 0.95%, 14.4%), 11.7% (95% CI 2.7%, 21.1%), 21.7% (95% CI 10.7%, 32.5%), and 16.1% (95% CI 3.3%, 28.8%) higher than the reference groups, respectively. Methylation levels were 2.2% (95% CI 0.64%, 3.7%) lower for every 1 unit increase in FCI and greater by 0.45% (95% CI 0.08%, 0.82%) for every fatigue T score unit increase. Conclusions: OPRM1 methylation levels varied by several patient factors. Further studies are warranted to replicate these findings and determine potential clinical utility.